A difusão nos canais de comunicação do Arquivo Público do Estado do Amazonas - Oliveira, Thiago da Luz (Brasil, 2024)
The present research aims to understand how dissemination is implemented in the Public Archive of the State of Amazonas – APEAM, through its communication channels. Through descriptive research, which was based on a literary review for scientific basis and the collection of data on communication channels through observation. In order to understand the broad perspective of the functioning and importance of Public Archives, with emphasis on the existence and appreciation of Diffusion, not only as a portrait of the reality of a state public institution through its communication channels, but also as a source of reflections on its potential in society, with contributions to future academic work in the area of Archivology.